An international relations discipline for tempestuous times. - Tanyag, Maria (Australian Journal of International Affairs, 2025)
In the face of tremendous violence and multiple crises, we are reminded that ours should not only be a discipline that examines crises, but also one that actively contributes to their resolution. What does IR as a discipline owe—or what must we give—to the pressing concerns of our times? What do we, in IR, owe to each other as a scholarly community or professional class? This essay argues for a reinterrogation of our discipline's relationship with 'crisis' as subject matter, method and motivation. It also makes a case for paying greater attention to our obligations to society and to one another as public intellectuals in need of collective methods to think across political and disciplinary divides.